High throughput phenotyping approaches – New era of fruits improvement - Shankar, Kripa; Wangchu, Lobsang; Singh, Senjam Romen; Singh, Barun; Devachandra, Nongthombam; Angami, Thejangulie (Indian Horticulture, 2020)
The first step in the analysis of a trait of an organism is the determination of the type and/or the level of expression of the concerned trait; this is referred to as phenotyping. In general, accurate phenotyping is far more difficult than accurate genotyping for a variety of reasons, including the vast number of phenotypic traits (mostly in the case of fruits) and their sensitivity to the environmental factors. Many biological investigations, including mutant isolation, genomic selection, genomewide association studies, and selection in plant breeding populations, require evaluation of thousands of lines/plants within a short period of time. Acquisition of sufficient relevant phenotype data of fruits/orchards are still challenging, especially for quantitative traits like tolerance to abiotic stress, polygenic disease resistance, and yield potential. Plant phenomics is described, as the study of plant growth, architecture, performance, and composition using high-throughput methods of data acquisition and analysis. The chief advantage of high-throughput phenomics approaches in fruits is the speed of data collection as field data that may take several days for acquisition by traditional approaches can be gathered in few hours using multiple sensors mounted onto a couple of vehicles (a field-based phenotyping platform). This would save time and allow multiple observations of a given fruit tree/Orchard in a single day. Phenomics is an area of intense ongoing research. The existing phenomics tools and techniques are being refined, their capabilities are being enhanced, and new approaches are being developed in different fruit crops.